PERUBAHAN BEBERAPA SIFAT KIMIA TANAH DAN PERTUMBUHAN TANAMAN JAHE MERAH SETELAH APLIKASI KOMPOS KULIT PISANG KEPOK PADA ULTISOL MASAM - SULEMAN, DARWIS (Jurnal Agroteknos, 2024)
The increasing need for red ginger as a raw material for medicines is a challenge for the farmers, but unfortunately ginger production is still lower than local and export demand. Basically, low soil fertility is a major obstacles in improving the productivity of ginger plants. This study aims to evaluate the changes of several soil chemical properties and the growth of red ginger plants treated with banana peel compost. This research was carried out at the Experimental Farm at the Faculty of Agriculture, Halu Oleo University from August to October 2021. This study used a randomized block design comprised of 4 treatments, namely K0 = no compost, K1 = 10 t ha-1 (400 g polybag-1), K2 = 20 t ha-1 (800 g polybag-1), K3 = 30 t ha-1 (1,200 g polybag-1) and repeated 4 times. The results revealed that the application of banana peel compost improved soil quality by increasing soil pH, organic C, CEC and total soil K. The improvements of soil properties were linear until the application of banana peel compost at 40 t ha-1. The application of banana peel compost has a significant effect on plant height and number of leaves and the impact was linear up to application of 30 t ha-1 (K3).